Influence of Mass Parameters Modification on Manoeuvrability of 9K33 „OSA” Set 9M33M3 Missile - Maciej K. CICHOCKI; Dariusz SOKOŁOWSKI; Zbigniew LEWANDOWSKI (Problemy Mechatroniki, 2020)
This paper discusses analytical method for realization of preliminary missile stability design calculations. Action has been taken to estimate influence of replacing massive blocks of analogue electronics with compact solutions of digital electronics in missiles remaining in operation. On an example of a short-range 9M33M3 missile from 9K33 „OSA” set and its previously analysed aerodynamic characteristics, the analysis of the centre of gravity location impact was carried out to determine maximum loads occurring in the two most interesting phases of flight: after booster engine burnout and directly after cruise engine burnout. The suggestion for modification suggestion of flight parameters’ optimization is presented which defines stability and its critical impact of these parameters on aeronautical engineering. For the tested missile, the methodology suggestions for the modification is discussed with the comparison of serially produced copies to define the ability of improving the flight parameters. The paper includes visualizations and quantity analysis of: maximal loads on the fuselage, minimal turn radius, and control wing inclination angle as missile’s angle of attack function.